Methodology for energy strategy to prescreen the feasibility of Ground Source Heat Pump systems in residential and commercial buildings in the United States. (December 2017) - Cho, Soolyeon; Ray, Saurabh; Im, Piljae; Honari, Hamed; Ahn, Jonghoon
Abstract: Geothermal resources have potential to reduce dependence on fossil fuels. The viability of geothermal heat pumps or ground source heat pumps (GSHPs) is significant as a potential alternative energy source with substantial savings potential. While the prospect of these systems is promising for energy efficiency, careful feasibility analysis is required before implementation. This paper presents the results of evaluation of the application feasibility for GSHPs in buildings across seven climate zones in three United States regions. A comprehensive methodology is developed to measure the integrated feasibility of GSHPs using compiled data for energy use intensity, energy cost and design parameters. Four different feasibility metrics are utilized: ground temperature, outdoor weather condition, energy savings potential, and cost benefits. For each metric, a corresponding feasibility score system is developed. The defined integrated feasibility score classifies the locations into five different feasibility levels ranging from Fair (0–20), Moderate (21–40), Good (41–60), High (61–80), and Very High (81–100). Conclusions show the GSHP feasibility level is High for 3 sites, Good for 8 sites and Moderate for 4 sites. Through the methodology, it is possible to develop a practical energy strategy for more economic and sustainable GSHP systems at an early design stage in the various viewpoints of geometries, climate conditions, operational factors, and energy costs. Highlights: Methodology for energy strategy is developed to prescreen the feasibility of GSHP systems in buildings in the US. Potential of GSHP systems for energy and cost savings over conventional ASHP systems is calculated. GSHP feasibility is examined by the analysis of given and built environments for all major climate regions. Results indicates that GSHP feasibility level is High for 3 sites, Good for 8 sites and Moderate for 4 sites. Methodology contributes to energy strategy for more economic GSHP systems at an early design stage.